Dari Timur Tengah Ke Nusantara: Sejarah Dan Jejak Mazhab Syafi’i Di Indonesia - Fitri Mardiani; Wisnu Subroto; Herry Porda Nugroho Putro; M. Rifky Maulani (Publikasi Berkala Pendidikan Ilmu Sosial, 2024)
Imam Syafi'i is one of the most influential scholars in the history of Islam, whose thoughts have shaped Islamic practices and traditions in Indonesia. Starting from Medina, where Imam Syafi'i established his madhab to the archipelago, this article traces the existence of the Syafi'i madhab with its traces in various aspects of religious life, such as worship, family law, and Islamic education. The method used is a literature study by sourcing books on the history of the life and thought of Imam Syafi'i, journals, and other research references. Based on the results of the literature review, it is known that Imam Syafi'I has left an invaluable legacy for Muslims in Indonesia. His moderate, inclusive, and balanced thinking between text and logic has underpinned various policies on Islamic law, theology, and life. This has shaped strong Islamic practices and traditions, seen in the unity of Muslims, social stability, and the development of Islamic science. So that through understanding the presence of Shafi'i thought, it can encourage the emergence of critical thinking in interpreting the existence of Islam that is proportional, tolerant, and in accordance with the needs of the times.